Two new species of Kaempferia L. (Zingiberaceae) from Cambodia and Lao PDR - Insisiengmay, Oudomphone; Newman, Mark Fleming; Haevermans, Thomas (European Journal of Taxonomy, 2020)
Two new species of Kaempferia L. (Zingiberaceae), Kaempferia nemoralis Insis. sp. nov. and Kaempferia pascuorum Insis. sp. nov., from Cambodia and Lao PDR are described and illustrated. Morphological similarities to their closely related taxa are discussed. Kaempferia nemoralis Insis. sp. nov. is compared with Kaempferia larsenii Sirirugsa in its vegetative parts, but distinguished by the following characters: whole plant taller, leaf sheath and young shoot apex green, petiole absent. It differs from Kaempferia rotunda L. in its floral parts by the following characters: presence of peduncle, floral tube longer, labellum purple with white line at centre, anther crest obovate, bifid, apex irregularly rounded and ovary glabrous. Kaempferia pascuorum Insis. sp. nov. is compared with Kaempferia larsenii Sirirugsa. Proposed IUCN conservation assessments are also given: Kaempferia nemoralis Insis. sp. nov. occurs in disturbed, open forest and is assessed as CR, whereas Kaempferia pascuorum Insis. sp. nov. occurs in short grassland and is assessed as EN.